2016
DOI: 10.2217/fon-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Chemoradiotherapy for Squamous Head and Neck Cancer: Cisplatin Versus Carboplatin? A Meta-Analysis

Abstract: Despite the trend to improved outcomes in using cisplatin, carboplatin is also active and can be a reasonable option to treat patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Since, survival benefit associated with concurrent chemoradiation is mainly due to improvement in locoregional control; multiagent radiosensitizing regimens may actually do better than single agent cisplatin. This is supported by the reversal in pattern of failure from locoregional recurrences to distant disease as seen in some of the studies that utilized multiagent regimens . MACH‐NC meta‐analysis on the use of chemotherapy also concluded that polychemotherapy either with platin or 5‐FU was not inferior to mono‐platin .…”
Section: Discussionmentioning
confidence: 86%
“…Since, survival benefit associated with concurrent chemoradiation is mainly due to improvement in locoregional control; multiagent radiosensitizing regimens may actually do better than single agent cisplatin. This is supported by the reversal in pattern of failure from locoregional recurrences to distant disease as seen in some of the studies that utilized multiagent regimens . MACH‐NC meta‐analysis on the use of chemotherapy also concluded that polychemotherapy either with platin or 5‐FU was not inferior to mono‐platin .…”
Section: Discussionmentioning
confidence: 86%
“…Carboplatin is anecdotally noted to be less toxic to the inner ear and kidney than cisplatin, but the efficacy of this drug in comparison to cisplatin is unknown. A recent meta-analysis of studies using cisplatin or carboplatin found no statistically significant difference in response rate between the two drugs, though the study may have been underpowered (Aguiar et al, 2016).…”
Section: Existing Studies On Cisplatin Ototoxicity In Head and Neck Cmentioning
confidence: 99%
“…Several studies have compared carboplatin alone and cisplatin alone for the chemoradiation of head-and-neck cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Some of these studies were additionally included in one or two meta-analyses from 2016 [ 46 , 47 ]. However, the results of the studies and meta-analyses were conflicting.…”
Section: Discussionmentioning
confidence: 99%